What Contributes to the Development and Maintenance of School Refusal in Chinese Adolescents: A Qualitative Study - Liu, Liang; Gu, Hong; Zhao, Xudong; Wang, Yanbo (Frontiers in Psychiatry, 2021)
Objective: Although there has been a growing number of studies on school refusal in Western cultures, the underlying factors that contribute to school refusal in Chinese adolescents remain unclear. This study aimed to better understand why Chinese adolescents refuse to go to school and to further interpret what they want to express through their school refusal behaviors. Methods: We performed a qualitative study using an interpretative phenomenological analysis. Twenty adolescents with school refusal experiences were recruited from the clinical psychology department of two mental health hospitals in Shanghai, China. They participated in semistructured, face-to-face in-depth interviews. The interviews were transcribed verbatim and analyzed according to the guidelines of interpretative phenomenological analysis. Findings: Five main superordinate themes emerged from data analysis: (a) competition-oriented social environment; (b) family living space dominated by conflicts; (c) personal living space lacking meaningful support; (d) conflict between the pros and cons of being labeled a psychopath; and (e) reintegration in school life. Conclusions: Our analysis emphasized the complex interacting effects of the social environment, family interpersonal conflicts, personal psychological factors and mental health complaints on the development and maintenance of Chinese adolescents’ school refusal. These factors contributed to school refusal at each level and influenced each other’s effects on school refusal behaviors. Therefore, interventions for Chinese teenagers with school refusal may need to integrate strategies that inspire reorganization and changes in different ecosystems, such as strategies related to government policy, peer relationships, family systems and individual inner dynamics.